BaTiO3 particles prepared by microwave-assisted hydrothermal reaction using titanium acylate precursors - Choi, GJ; Kim, HS; Cho, YS (ELSEVIER SCIENCE BV, 1999)
Microwave-assisted hydrothermal reaction to prepare barium titanate (BaTiO3) particles using titanium acylate precursors was investigated. Experimental variables taken into account in this study were the reaction type (reflux and autoclave), the reaction time and the Ba to Ti ratio in sol solutions. Autoclave reactions were more effective than reflux reactions in terms of time and barium utilization efficiency, in both type reactions, the variation in Ba to Ti ratio in sol solutions led to substantial changes in particle morphology as well as Ba:Ti stoichiometry in resulting particles. Mechanisms for those changes were proposed. Characterization of synthesized particles were performed via SEM, XRD, Raman, XPS and elemental analysis based on ICP. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: BARIUM-TITANATE